Familial hypercholesterolaemia: cascade testing and monogenic vs. polygenic causes - Humphries, Steve (Henry Stewart Talks, 2023)
Familial hypercholesterolaemia, UK FH-NICE guidelines, Cascade testing of family members, Genetic testing for FH, Genetic causes of FH in the UK, Monogenic causes of FH phenotype, Polygenic causes of FH phenotype, Clinical consequences of monogenic vs. polygenic causes